CALCULATING THE CARBON FOOTPRINT FOR ENVIRONMENTAL SUSTAINABILITY: THE CASE OF TED DİYARBAKIR COLLEGE (TÜRKİYE) - Ozerdem, Sena; Ozerdem, Mehmet Sirac (PROFESSIONAL STUDIES: Theory And Practice, 2024)
It is crucial to promote awareness, particularly throughout society, regarding a topic that holds significant importance for our environment. This study was undertaken with the intention of making a contribution to research on carbon footprint, driven by this motive. In this study, the carbon footprint calculation of TED Diyarbakır (Türkiye) College was made using the IPCC Tier approach. The carbon footprint of 3 different capabilities, namely scope 1 (Natural gas, gasoline, diesel, fire extinguishers), scope 2 (electric) and scope 3 (Water consumption, services), were calculated. When Scope 1, Scope 2 and Scope 3 are evaluated together, it is seen that the amount of carbon footprint originating from Scope 1 is higher. Sources of emissions from Scope 1 include natural gas consumption, diesel and gasoline fuel consumption, as well as fire extinguishers. When the emission sources in the college were compared, it was determined that the highest carbon footprint was due to natural gas consumption within scope 1 (97.98%). Subsequently, it was determined that the carbon footprint was caused by existing vehicle shuttle within scope 3 (1.917%). Finally, it has been determined that the carbon footprint is caused by the existing electricity consumption within scope 2 (0.1%). It is stated that there are 2 reasons for the low carbon footprint caused by electricity consumption. The first is that the equipment used in lighting is LED, and the second is that there is no need for lighting fixtures due to the long lighting time of the day in our geography.